Actual Problems of Kazakh History. Review of the Book by K.A. Pishchulina “Essays on the History of the Kazakh Khanate” - A.A. Galiyev (Золотоордынское обозрение, 2017)
A collection of articles written by a well-known orientalist-historian K.A. Pishchulina and published in 2016 includes papers of different years, written on the basis of Persian and Turkic sources reflecting the most pressing issues related to Kazakh khanate. The publishing of this work immediately became a major event in historical scholarship of Kazakhstan. During the Soviet period, the history of this state, as well as of other states created by nomadic peoples, remained poorly understood. Many questions were debatable, since Marxism-Leninism, which was in forefront of science, could not adapt the formational class theory for a nomadic society and nomadic mode of production etc. However, some researchers, including K.A. Pishchulina, were already thinking about these issues. Particularly she studied the role of Turkestan cities as part of Kazakh khanate. According to her main findings, these cities performed a variety of functions being centers of handicraft production, agriculture and trade. As for Turkestan city itself, it was capital and spiritual center of the state, and the management of settled-agricultural population was carried out by various officials. Furthermore, the collection of Pishchulina’s papers discusses management system of nomadic population, tax system of the Khanate. The author comes to a justified conclusion that monetary system needs to be studied further. Next major issue relates to mythologization of Turkic peoples’ history. The books written by amateurs assert that the Golden Horde was a part of Khanate, and Chinggis Khan was a Kazakh. Therefore, several Pishchulina’s articles were published in order to expose these myths. Thus, in this collection the reader would find answers to a variety of questions related to the history of Kazakhstan and adjacent territories and its impact in modern times.